2003
DOI: 10.1021/bi026907m
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State and Pre-Steady-State Kinetic Analysis of Halopropane Conversion by a Rhodococcus Haloalkane Dehalogenase

Abstract: . (2003). Steady-state and pre-steadystate kinetic analysis of halopropane conversion by a Rhodococcus haloalkane dehalogenase. Biochemistry, 42(26), 8047-8053.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 37 publications
(67 reference statements)
2
33
0
1
Order By: Relevance
“…e Determined at pH 8.2 and 30°C (31). f Determined at pH 9.4 and 30°C (14). g Determined at pH 8.6 and 37°C (this study).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…e Determined at pH 8.2 and 30°C (31). f Determined at pH 9.4 and 30°C (14). g Determined at pH 8.6 and 37°C (this study).…”
Section: Discussionmentioning
confidence: 75%
“…The main and very important difference in kinetic mechanism is in the rate-limiting step. Whereas the halide release is the predominant rate-limiting step of DhlA (8) and liberation of alcohol is the rate-limiting step of DhaA (14) under steady-state conditions, the release of both halide and alcohol was found to be fast in the catalytic cycle of LinB. The conclusion that there are different rate-limiting steps for three enzymes from the same protein family sharing the same chemical mechanism demonstrates that extrapolation of this important catalytic property of one enzyme to another can be misleading, even for evolutionary closely related proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Steady-state kinetic constants were determined for DmmA short (Table II), which revealed that these parameters are comparable to other HLDs. 15,27,29 DhlA has threefold greater catalytic efficiency than DmmA for 1,3-dibromopropane (fourfold lower k cat , 12-fold lower K m ), 27 whereas…”
Section: Hld Activitymentioning
confidence: 99%
“…The differences in the substrate specificities of these three haloalkane dehalogenases can be accounted for on the basis of their three-dimensional structures (11). Comparison of the kinetic mechanisms of DhlA, DhaA, and LinB showed that the overall reaction mechanisms are similar but that the rate-limiting steps differ, i.e., halide release in the case of DhlA (44), liberation of an alcohol in the case of DhaA (4), and hydrolysis of an alkyl-enzyme intermediate in the case of LinB (41). Partial improvement in the catalytic properties and modification of the substrate specificities of haloalkane dehalogenases by rational design (5,34) and directed evolution approaches (3,40) have recently been reported.…”
mentioning
confidence: 99%